Manajemen Kurikulum dalam Mengintegrasikan Muatan Lokal Berbasis Pesantren di TK Darus Sholah - Tsaltsa Nisa'ul Khoiroh (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to describe curriculum management in integrating pesantren-based local content at TK Darus Sholah Jember. Islamic education in early childhood is considered important to be developed in accordance with the identity and culture of the institution, especially those within the pesantren environment. Therefore, comprehensive curriculum management is needed so that pesantren local content can be integrated with the national curriculum and support the formation of Islamic character in children from an early age. This research uses a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. The research subjects consist of the principal, vice principal for curriculum, teachers, and parents as supporting informants. The findings show that curriculum management covers four main aspects planning through annual meetings with the principal and teachers; organizing with clear division of tasks and parental involvement implementing local content in daily activities and Islamic celebrations with child-friendly approaches and creative media and conducting regular evaluations by teachers, the principal, the foundation, and parents. The conclusion emphasizes that the integration of pesantren-based local content at TK Darus Sholah is not merely ceremonial but is systematically embedded in the institution’s curriculum, thereby strengthening children’s spiritual development alongside general knowledge.
:: Finalisasi file repositori 21 Juli 2026_Kurnadi
Keywords: curriculum management; local content; pesantren; early childhood education